Analysis of cardiac left-ventricular volume based on time warping averaging - Caiani, E. G.; Porta, A.; Baselli, G.; Turiel, M.; Muzzupappa, S.; Pagani, M.; Malliani, A.; Cerutti, S. (Medical & biological engineering & computing, 2002)
The cardiac left-ventricular (LV) volume signal, obtained by acoustic quantification, is affected by noise and respiratory modulation, resulting in a large beat-to-beat variability that affects the computation of LV function indices. A new method is proposed to improve the evaluation of LV indices by applying a signal averaging technique based on dynamic time warping to consecutive LV volume waveforms. Volume signals obtained from ten normal young (NY) subjects (mean age +/- SD: 25+/-5 years) were used to evaluate the performance of this algorithm. To evaluate its clinical utility, the effects of ageing and pharmacologically induced changes on LV function were assessed by studying, respectively, ten normal (N) adult subjects (age 64+/-8 years) and ten patients with dilated cardiomyopathy during a control and low-dose dobutamine (10 microg kg(-1) min(-1)) study. Indices of LV function were highly consistent, with a variability of less than 8%, even when only 16 beats were averaged, independently of their selection inside the whole recording. When compared with beat-to-beat measures, the averaging of 16 beats significantly reduced (by more than 50%) the interbeat variability of all indexes. Expected alterations in both diastolic and systolic function were evidenced both with ageing (peak filling atrial contraction and ejection rates: from 275+/-77 mls(-1), 76+/-30 ml s(-1) 230+/-70 mls(-1), respectively, in NY, to 160+/-33 mls(-1), 125+/-39 mls(-1), 163+/-54 mls(-1) in N) and with dobutamine (peak filling and ejection rates from 160+/-72 mls(-1) and 183+/-86 mls(-1) respectively, in control, to 253+/-75 mls(-1) and 251+/-105 mls(-1) with dobutamine). Signal averaging with time warping allows fast and improved assessment of LV function.